Child labour and violence among street children in Anambra State: Implication on access to education - Ozoh, Joan Nwamaka; Uzoechina, Benedict Ikemefuna; Imoagwu, Chika Pricillia; Madueke, Chinwe Monica (Journal of Management, Economics, and Industrial Organization, 2022)
Street children are exposed to violence, rape, abduction, neglect, physical and mental abuse. These violent experiences, combined with the constant insecurity of having to struggle to find food and shelter, rob these children of their fundamental rights and opportunities to attain full and best life potentials. This study, therefore, evaluated the impact of child labour and violence on the ability of street children to have access to education as well as the effectiveness of co-ordination and collaboration efforts of stakeholders in curbing child labour and violence in Anambra state. The data for the study were collected through the use of interview schedule and questionnaire and were analyzed through descriptive and multinomial logistic regression methods. Results showed that child labour had significant but negative impact on the ability of street children to go to school while child violence is negative but non-significant. The significance of child labour is further confirmed by the long hours and high frequency on the street by street children, thus making it difficult for them to succeed in school. Results further show that there is coordination failure among stakeholders. The study recommends very strong political will to implement child rights’ laws and encourages citizens’ vigilance/responsibility towards reporting child abuse, labour and violence.